2017
DOI: 10.1097/md.0000000000006235
|View full text |Cite
|
Sign up to set email alerts
|

The optimal exhaled concentration of sevoflurane for intubation without neuromuscular blockade using clinical bolus doses of remifentanil

Abstract: Background:The aim of this study was to investigate the optimal exhaled sevoflurane concentration that produces adequate endotracheal intubation conditions when sevoflurane is combined with the different bolus doses of remifentanil used in clinical practice.Methods:The patients were randomized to 3 groups (groups 1.0, 1.5, and 2.0), receiving remifentanil bolus doses of 1.0, 1.5, and 2.0 μg/kg, respectively. For each group, the concentration of sevoflurane used for each consecutive patient was increased or dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…[ 3 , 4 , 6 ] Pretreatment with remifentanil during induction has some advantages. The optimal dosage of remifentanil pretreatment can offer hemodynamic stability during maneuvers in the induction period, including laryngoscopy and intubation, [ 9 , 10 ] and it was also shown to have protective effects on organs in animal studies. [ 13 15 ] In addition, it is reported that remifentanil pretreatment can prevent pain caused by propofol injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 3 , 4 , 6 ] Pretreatment with remifentanil during induction has some advantages. The optimal dosage of remifentanil pretreatment can offer hemodynamic stability during maneuvers in the induction period, including laryngoscopy and intubation, [ 9 , 10 ] and it was also shown to have protective effects on organs in animal studies. [ 13 15 ] In addition, it is reported that remifentanil pretreatment can prevent pain caused by propofol injection.…”
Section: Discussionmentioning
confidence: 99%
“…Pretreatment with remifentanil can decrease injection pain [ 8 ] and provide hemodynamic stability during the induction period. [ 9 , 10 ] However, the required bolus dose of propofol for loss of consciousness during induction in patients who receive pretreatment with remifentanil or midazolam remains unclear. Furthermore, the effects of premedication with remifentanil or midazolam on the patient's hemodynamics have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“… 5 The time required to reach an equilibrium between alveolar and target organ concentrations is 9–12 minutes. 9 , 17 Thus, we maintained the end-tidal sevoflurane concentration for 15 minutes before we assessed the response of subjects. Many factors influence the efficacy of inhaled anesthetics, including age, 18 , 19 temperature, 20 hypotension, acid-base status, 21 diabetes, 22 and sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…According to the previous studies, the mice received the 3% sevoflurane anesthesia 2 hours daily at 6, 7, 8 day after birth to mimic the clinical several times anesthesia 14,35,36 ,which is reported to induce the neurotoxicity and further cognitive function defect 2,37 . 3% is also the clinical concentration of sevoflurane for anesthesia 38 . The hippocampus tissues of mice were harvested at the end of the sevoflurane anesthesia administration.…”
Section: Methodsmentioning
confidence: 99%